Teachers’ Skills Preference in Teaching Oral Presentations to Technical Students - Noor Raha, Mohd Radzuan; Abdullah Adnan, Mohamed; Nor Ashikin, Abdul Aziz (2015)
Higher education institutions (HEI) are entrusted with the responsibility to equip students with essential employability skills to function well in the workplace. Preparing HEI students with oral communication competency particularly oral presentation skill is crucial because research studies found that delivering oral presentations is one of the most frequent communicative events held at the workplace (DeKays, 2012; Yusof, 2012; Kassim and Ali, 2010). However, Kunioshi et. al (2014) argue that the teaching of oral communication skills are more complex and challenging. In such situation, language instructors would have employed various ways in teaching the skills to the students. Therefore, this study aims to investigate the language instructors' teaching emphasis and preferences in the teaching of oral presentation skills in classrooms. A quantitative research methodology will be applied in this study in which a set of questionnaire were distributed to 50 Universiti Malaysia Pahang (UMP) English language instructors who are currently teaching English courses in UMP. The findings of this study reveal that the language instructors place different emphasis and preferences with regard to content, language and delivery components while teaching oral presentation skills. This study will also discuss the implications of its findings on the teaching and learning of oral communication skills specifically oral presentation skills in higher education context.